eIF4E1 Regulates Arabidopsis Embryo Development and Root Growth by Interacting With RopGEF7 - Liu, Taibo; Liu, Qianyu; Yu, Zhen; Wang, Chunling; Mai, Huafu; Liu, Guolan; Li, Ruijing; Pang, Gang; Chen, Dingwu; Liu, Huili; Yang, Jiangyi; Tao, Li-Zhen (Frontiers in Plant Science, 2022)
Eukaryotic translation initiation factor 4E1 (eIF4E1) is required for the initiation of protein synthesis. The biological function of eIF4E1 in plant–potyvirus interactions has been extensively studied. However, the role of eIF4E1 in Arabidopsis development remains unclear. In this study, we show that eIF4E1 is highly expressed in the embryo and root apical meristem. In addition, eIF4E1 expression is induced by auxin. eIF4E1 mutants show embryonic cell division defects and short primary roots, a result of reduced cell divisions. Furthermore, our results show that mutation in eIF4E1 severely reduces the accumulation of PIN-FORMED (PIN) proteins and decreases auxin-responsive gene expression at the root tip. Yeast two-hybrid assays identified that eIF4E1 interacts with an RAC/ROP GTPase activator, RopGEF7, which has been previously reported to be involved in the maintenance of the root apical meristem. The interaction between eIF4E1 and RopGEF7 is confirmed by protein pull-down and bimolecular fluorescent complementation assays in plant cells. Taken together, our results demonstrated that eIF4E1 is important for auxin-regulated embryo development and root growth. The eIF4E1–RopGEF7 interaction suggests that eIF4E1 may act through ROP signaling to regulate auxin transport, thus regulating auxin-dependent patterning.